Ageing at work: how to design a lifelong workplace? - Ramos, S.; Carvalho, H. (8th International Conference on Applied Human Factors and Ergonomics, 2017)
Background: Ageing of the workforce is perhaps the greatest current issue to which European societies are being challenged to respond. The common solution aims to encourage ageing workers to remain active but this cannot be achieved without an adjustment of working conditions, considering their health and needs (Vendramin, Valenduc, Molinié, Volkoff, Ajzen & Léonard, 2012). Despite the increasing attention to demographic trends, the study of the relationship between age and work has remained at a macro level with little impact on what happens inside the organizations, namely regarding the working conditions design. The fact that ageing is a challenge for design is not new (Haigh, 1993), neither the implications of age changes (both in physical and cognitive aspects) for ergonomic design (Imrhan, 1993). However, the complex relationship between age and work goes beyond the association between the exposure to risk factors and early aging, and only few studies attempt to encompass this complexity and try to put this discussion in a temporal dimension, considering the developments of health and work over lifetime. Some studies have already shown the positive effects of ergonomic interventions to reduce work related health problems in order to preserve the workers’ health status (May, Reed, Schwoerer & Potter, 2004) and prevent the early age losses. Based on several European studies, we developed a survey and conducted a research among active Portuguese workers in order to monitor working conditions and health issues taking into account job modifications and age evolution. Method: The survey includes dimensions focuses on working conditions (working time, schedules, demands/resources, perceived risks); health complaints (and their relation with work); and questions about retirement expectations, health and safety organizational policies, job redesign and individual measures due to age. Our sample comprises 3106 active workers from all activity sectors, aged between 18 and 76 (M =39.80 and SD =10.32); 44.6% are males and 54.4% are females; 92.5% have a full time job; 75.2% are permanent workers; 62.5% work in SME*(micro=15.8%; small=21.9%; medium=24.8%) and 35% in big companies. Results: Data analysis is still in course, but the first results show that there’s a clear incongruence between the proportions of workers that relate health problems, incapacities formally recognised or early retirement situations due to health conditions and the very low proportion of individual measures proposed by the company due to age. In fact, there’s a lack of intervention at the workplace level that go along with the evolutions of workers characteristics and needs during their life course. Discussion/Conclusion: This study will contribute to stress the importance of ergonomic design in order to develop working situations that can be adapted to an ageing workforce. This adaptation is a crucial aspect to reduce the exposure to working conditions, preserve health and work capacity and allow a sustainable work.